Pengaruh Variasi Konsentrasi Larutan Buah Maja (Aegle Marmelos) sebagai Insektisida Alami dalam Mengendalikan Walang Sangit (Leptocorisa Acuta) di Desa Rancak Lombok Tengah - Kharisma Amrilla; Edi M Jayadi; Mukminah (Jurnal Multidisiplin Madani, 2022)
The use of synthetic insecticides can cause environmental pollution problems and can make pests resistant. For this reason, other alternatives are sought in the form of natural insecticides. This study aims to determine the effect of the concentration of maja fruit solution as a natural insecticide in suppressing rice bugs that land on rice plants and suppressing damage to rice grains. This study used RAL with 4 treatments, namely a concentration of 40%, 50% 60% and control and 5 replications. The samples used were ± 200 walang sangit tails. The results obtained showed that the maja fruit solution with a concentration of 60% had an effect on suppressing the walang sangit that landed on an average of 1 head and suppressing the damage of rice grains with an average of 10 grains of rice. So the results obtained indicate that the concentration of the maja fruit solution has an effect on controlling the walang sangit.